Commentary—A United Front: Using the Range of Psychological Variance in Cutting‐Edge Practice and Emerging Research. Issue 147 (March 2015) - Jackson, Simon Anthony; Kleitman, Sabina
Abstract: Psychological and behavioral variance can be explained by differences in the environment, and between and within individuals. Almost 60 years ago, Cronbach (1957) called for converging investigations into all three sources as important for the development of accurate science and useful applications in the real world. Yet rifts among researchers tackling these various sources still exist. The articles in this issue, for example, differ greatly in terms of content, methodological approaches, and the sources of variance being addressed. On the basis of these articles, this commentary seeks to reignite Cronbach's call as an important step for psychological research to progress as a unified and useful science. © 2015 Wiley Periodicals, Inc.